Metabolism of Alzheimer beta-amyloid precursor protein: regulation by protein kinase A in intact cells and in a cell-free system. - Xu, H (1996)
Various compounds that affect signal transduction regulate the relative utilization of alternative processing pathways for the beta-amyloid precursor protein (beta APP) in intact cells, increasing the production of nonamyloidogenic soluble beta APP (s beta APP) and decreasing that of amyloidogenic beta-amyloid peptide. In a recent study directed toward elucidating the mechanisms underlying phorbol ester-stimulated s beta APP secretion from cells, it was demonstrated that protein kinase C increases the formation from the trans-Golgi network (TGN) of beta APP-containing secretory vesicles. Here we present evidence that forskolin increases s beta APP production from intact PC12 cells, and protein kinase A stimulates formation from the TGN of beta APP-containing vesicles. Although protein kinase A and protein kinase C converge at the level of formation from the TGN of beta APP-containing vesicles, additional evidence indicates that the regulatory mechanisms involved are distinct.